2016
DOI: 10.1002/admi.201600254
|View full text |Cite
|
Sign up to set email alerts
|

High‐Aspect‐Ratio Parallel‐Plate Microchannels Applicable to Kinetic Analysis of Chemical Vapor Deposition

Abstract: growth rates within the 3D features are in proportion to the concentrations of fi lmforming species (i.e., a source precursor or intermediate species generated from a precursor), under the assumption that the deposition reaction on the surface follows fi rst-order reaction kinetics, as is common in most low-pressure (LP) CVDs. In most LP-CVDs, the mean free path of the fi lm forming species is much larger than the feature size, so the governing mass-transport mechanism is Knudsen diffusion, and the gas-phase r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 58 publications
(68 reference statements)
0
12
0
Order By: Relevance
“…The bare HAR microchannels were prepared using a method described elsewhere, 17 and are shown in Figure 1(a). The manufacturing procedure is as follows: part of the Si substrate is shallow-etched by reactive-ion etching, followed by stacking with another planar Si substrate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bare HAR microchannels were prepared using a method described elsewhere, 17 and are shown in Figure 1(a). The manufacturing procedure is as follows: part of the Si substrate is shallow-etched by reactive-ion etching, followed by stacking with another planar Si substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Here, adding arbitrary underlayers to the vertical 3D test structures is not feasible because it imposes conformal deposition of the underlayer materials onto the micropores. By contrast, conformal deposition of underlayer materials onto a lateral HAR 3D test structure that we developed (denoted a microchannel 17 ) is possible because it is assemblable, and underlayers can be formed uniformly before assembling the microchannel. Note that numerous studies on conformal CVDs and ALDs to date assumed that the film formation started simultaneously at the beginning of the gas supply at all locations (i.e., at inlet and bottom of the trench, upstream and downstream of the reactor).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, for micromold injection, the plastic devices bear quite high temperature and pressure in the thermal bonding step, which is also prone to collapse the rectangular channel. Though clamping can be used instead of permanent bonding to preserve the high-aspect-ratio channels, [23] it also makes the device complex, which limits the application of such microchannels compared to compact rectangular microtubes. Considering the intrinsic pullback of the above two-step methods for producing high-aspect-ratio rectangular microchannels, the airassisted microextrusion is very advantageous as a onestep method.…”
Section: Introductionmentioning
confidence: 99%
“…Application of the NCD deposition methods to industrial application requires deposition on structured substrates, with high aspect ratio features to determine the process's limitations. In addition, threedimensional patterned substrates are a useful tool for the study and modelling of CVD growth [15][16][17], which is still not fully understood. Floter et al [18] in 1995, reported a strong dependence of the nucleation density on the orientation of the surface when bias pre-treatment of structured Si substrate was employed.…”
Section: Introductionmentioning
confidence: 99%